Avaliação tomográfica quantitativa em doença pulmonar obstrutiva e restritiva crônica pelo índice do pulmão normal - Barros, Marcelo Cardoso (2022)
Purpose: Our objective was to evaluate whether the normal lung index (NLI) from quantitative computed tomography (QCT) analysis can be used to predict mortality as well as pulmonary functional tests (PFTs) in patients with chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD). Materials and Methods: Normal subjects (n = 20) and patients with COPD (n = 172) and ILD (n = 114) who underwent PFTs and chest CT were enrolled retrospectively in this study. QCT measures included the NLI, defined as the ratio of lung with attenuation between –950 to –700 Hounsfield units (HU) over total lung volume (-1024 to -250HU, mL), high-attenuation areas (–700 to –250 HU, %), emphysema index (< –950 HU), Skewness, Kurtosis, and mean lung attenuation. Coefficients of correlation between the QCT measurements and PFT results in all subjects were calculated. Univariate and multivariate survival analyses were performed to assess mortality prediction by disease, as well Kaplan-Meier curves. Results: Pearson’s correlation analysis showed that the NLI correlated moderately with the forced expiratory volume in 1 s in subjects with COPD (r = 0.490, p < 0.001) and the forced vital capacity in subjects with ILD (r = 0.452, p < 0.001). Multivariate analysis revealed that the NLI of < 70 % was a significant independent predictor of mortality in subjects with COPD (HR = 3.14, p = 0.034) and ILD (HR = 2.72, p = 0.033). In the COPD group, the 5-year mortality for patients with NLI < 70% versus NLI > 70 % was, respectively, 27.8 % and 13.5 % (p = 0.002). In the ILD group, the 5-year mortality for patients with NLI < 70 % versus NLI > 70 % was, respectively, 40.7 % and 29.9 % (p = 0.05). Conclusion: QCT analysis, specifically the NLI, can also be used to predict mortality in individuals with COPD and ILD.